2008
DOI: 10.1038/ejhg.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

Catechol O-methyl transferase and dopamine D2 receptor gene polymorphisms: evidence of positive heterosis and gene–gene interaction on working memory functioning

Abstract: The COMT Val 108/158 Met polymorphism has been extensively studied in relation to individual differences in working memory (WM) performance. The present study tested the association of the COMT Val 108/158 Met polymorphism with WM performance in two independent family-based Dutch samples: 371 children (mean age 12.4 years) and 391 adults (mean age 36.2 years). A significant association was found between the COMT polymorphism and WM scores in the combined adult and young cohorts. The association reflected posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
0
45
1
Order By: Relevance
“…Met:Met isoform was also associated with episodic memory and recall, but not with semantic memory, fluency, or knowledge (de Frias et al 2004); as well as with improved executive function, measured by verbal fluency, working memory, and Tower of Hanoi (de Frias et al 2005). However, subjects with the Val:Met isoform have also been found to have better performance on memory tasks over homozygotes (Gosso et al 2008;Harris et al 2005). There have also been findings of no association between COMT and performance on a range of other cognitive tests (O'Hara et al 2006;Ho et al 2005;Reuter et al 2005).…”
Section: Comtmentioning
confidence: 89%
See 2 more Smart Citations
“…Met:Met isoform was also associated with episodic memory and recall, but not with semantic memory, fluency, or knowledge (de Frias et al 2004); as well as with improved executive function, measured by verbal fluency, working memory, and Tower of Hanoi (de Frias et al 2005). However, subjects with the Val:Met isoform have also been found to have better performance on memory tasks over homozygotes (Gosso et al 2008;Harris et al 2005). There have also been findings of no association between COMT and performance on a range of other cognitive tests (O'Hara et al 2006;Ho et al 2005;Reuter et al 2005).…”
Section: Comtmentioning
confidence: 89%
“…Differences in study results may be due to differences in age, as well as other potential interactions as few studies were in generally healthy populations. It has previously been found that an interaction between the activity of COMT and the expression of dopamine receptors such as DRD2 has an effect on cognitive function (Gosso et al 2008;Reuter et al 2005;Xu et al 2007). …”
Section: Comtmentioning
confidence: 97%
See 1 more Smart Citation
“…First off, regarding fronto-striatal genetics, gene-gene interactive effects between the COMT polymorphism and the TaqIA-ANKK1 polymorphism are consistently reported in working memory tasks (Reuter et al, 2005;Gosso et al, 2008;Stelzel et al, 2009Stelzel et al, , 2010Garcia-Garcia et al, 2011;Wishart et al, 2011;Berryhill et al, 2013). Two studies reported higher stability and accuracy of task-relevant representations during delays and lower interference in Met/A1 carriers compared to Val/A1 carriers.…”
Section: Da Metabolization (Catechol-o-methyltransferase)mentioning
confidence: 95%
“…The condition in which heterozygotes show better functioning than homozygotes for quantitative traits is usually referred to as positive heterosis. Positive heterosis is common in humans and has been reported for the influence on cognitive function of the catechol O-methyl transferase genetic polymorphism [21]. An earlier study demonstrated a lower proportion of MTHFR C677T heterozygotes among the mothers of nonsyndromic cleft lip probands, showing a heterozygote advantage [22].…”
Section: Discussionmentioning
confidence: 99%